Extraction of pectin from pomelo peels using conventional heating, ultrasonic, microwave and subcritical water techniques / Liew Shan Qin - Liew , Shan Qin (2019)
Citrus fruit peels can be converted into value-added products such as pectin and via the bioconversion to manage its disposal problems. Despite the wide utilization of pectin in the food industry, knowledge on pectin extraction process and its chemistry is limited. Therefore, this research was aimed to extract pectin from the peel of pomelo, the largest citrus fruit with its peel accounted for approximately 40% of its fruit weight, via different extraction techniques. The performances of various techniques were evaluated and the pectins obtained were compared via physicochemical properties and structural analyses. Conventional heating extraction (CE) method with citric acid as extraction solvent was first used to extract pectin from pomelo peel in the study. A Box–Behnken design was employed to optimize the yield and the degree of esterification (DE) of pectin. The optimized conditions were determined at pH 1.80, extraction time of 141 min, temperature of 88°C and liquid-solid ratio of 29:1 mL/g with a pectin yield of 39.13% and a DE value of 59.23%. The latter signifies a high methoxyl (HM) pectin was obtained. The extraction pH impacted pectin yield and its DE value greatly and pH of 1 – 2 resulted in diverse pectin functional groups with different structural modifications. The feasibility of non-conventional extraction methods such as ultrasound (UAE), microwave (MAE), ultrasound-microwave (UMAE), and microwave-ultrasound (MUAE) assisted extraction to extract pectin from pomelo peel using citric acid were also studied. All these methods also gave HM pectin with UMAE achieved the best yield (36.33%) followed by MUAE (31.57%), MAE (30.24%) and UAE (13.24%). The optimized conditions of UMAE were determined at pH 1.80, 27.52 min sonication and 6.40 min microwave irradiation at 643.44 W. In UMAE, pH exerted a significant impact on pectin yield while microwave power on DE value. The combined extraction technique i.e. UMAE and MUAE gave better galacturonic acid (GalA) content (> 65%) than that obtained from sole extraction technique (i.e. UAE or MAE). Furthermore, the morphological structures of pectin were affected by the technique and the sequence of the combined extraction methods; i.e. pectin extracted from MUAE closely resembled to that of MAE whereas it was smaller with more regular surface if subjected to ultrasonication before microwave as in UMAE. In addition, pectin was extracted in an acid free and environmental friendly subcritical water extraction (SWE) system. The SWE yielded 19.63% of pectin and a DE of 40.09% at optimized operating condition of 120°C and 30 bar. The extraction yield predominantly influenced by temperature. The absence of acid and a prolonged exposure to pressure under dynamic SWE conditions facilitated the formation of low methoxyl (LM) pectin. Compared with SWE, other extraction techniques incorporated with acid have higher pectin yields and greater DE values. Comparing the physicochemical properties of pectin extracted using different techniques, all of them possessed good quality within acceptable GalA limit (≥ 68%). They have close viscosity around ~0.01 Pa.s, molecular weight at ~8.20 × 10⁴ Da. Also, the pectin gels prepared from various extracted pectin exhibited pseudoplastic behavior. The pectin extracted from UMAE was lighter color and smaller in size. On the other hand, pectin extracted via SWE showed less acidity (pH 4.72) and better solubility attributed to its amorphous structure. In term of energy usage and efficiency, SWE consumed the highest energy at 1.0530 kW.h whereas UMAE achieved the highest efficiency at 0.4909 g/h. As a conclusion, UMAE is commendable to extract pectin from pomelo peel due to its operational efficiency.